KAJIAN RISIKO BENCANA ABRASI WILAYAH PANTAI KECAMATAN GALESONG, KABUPATEN TAKALAR - Andi Muhammad Alfian Arafat (Jurnal Sains dan Teknologi Tadulako, 2022)
Preliminary research on the risk assessment of coastal erosion in the Galesong District. The beach is an area between land and sea where various kinds of human activities are carried out in the coastal area. In the last few years, the abrasion disaster in the coastal area of Galesong District has continued to increase, so that the facilities and houses of the residents have been damaged. Disaster risk analysis is carried out to determine the value of disaster risk and develop strategies to reduce existing disaster risks. The data analyzed in the form of secondary data originating from the research literature at the location being studied as well as the database of agencies related to the population of the Galesong District. The risk value for coastal abrasion disaster in Galesong District was obtained, then a strategy was developed to reduce the risk value for coastal abrasion disaster in Galesong District.